The influence of emotional intelligence on job performance of administrators in UiTM. - Md Yusof, Rozman; Abu Samah, Bahaman; Mustapha, Ghazali; Ahmad, Shamsuddin (2007)
The purpose of this study was to investigate the relationships of the selected independent variables: emotional intelligence dimensions (self-management, relationship-management and communication) on job performance. This study also determined the extent to which job performance can be predicted by the independent variables.Data was collected from 152 randomly selected adntinistrators in UiTM, using self-administered questionnaires that comprised: (I) Management View/ Practices Questionnaire (100 items) that measured job performance and (2) People Index (74 items) that measured emotional intelligence. Overall, the study revealed that UiTM administrators' job performance and its dimensions were high. The level of total emotional intelligence and its dimensions: self-management, relationship-management and communication were relatively high. Results obtained from the correlation analysis revealed that the three emotional intelligence dimensions of the administrators were strongly related to job performance. Results from a Stepwise Regression analysis revealed that communication and relationship-management contributed significantly towards job performance. These two predictors explained 62% of the variance in job performance. To conclude, this study investigating the relationships of the multidimensional aspects of job performance and selected independent variables of the study appeared to provide significant results. When emotional intelligence is present, studies have shown that a significant part of an organization's profitability is linked to the quality of its work life, which is based largely on trust and loyalty within the organization. Studies of this nature have not been heavily dealt with in prior studies especially in a non-western environment like universities in Malaysia. Therefore, the study should be extended to include a larger population of administrators from other universities in Malaysia so that it would be able to provide stronger evidence on the applicability of western findings in the developing context.